Microvascular changes following four-hour single arteriole occlusion - Saltzman, Darin James; Kerger, Heinz; Jimenez, Juan Carlos; Farzan, Dina; Wilson, James M.; Thompson, Jesse E.; Intaglietta, Marcos (Microsurgery, 2013)
Background: Free tissue transplantations are lengthy procedures that result in prolong tissue ischemia. Restoral of blood flow is essential for free flap recovery; however, upon reperfusion tissue that is viable may continue to be nonperfused. To further elucidate this pathophysiology skeletal muscle microcirculation was investigated during reperfusion following 4-hour single arteriole occlusion. Materials and methods: A blunt micropipette probe was use to compress a single arteriole in the unanesthetized hamster (N = 20) dorsal skinfold chamber. Arteriole (n = 20), capillary (n = 97), and postcapillary venule (n = 16) diameters and blood flow were analyzed at 0, 30, 60, 120, 240 min and 24 hours of reperfusion after 4 hour occlusion. Results: Feeding arcade arterioles exhibited a brief (<10 min) vasoconstriction [0.31 ± 0.26 (mean ± SE) of baseline] upon reperfusion followed by a maximum vasodilation at 120 min (1.3 ± 0.10: P < 0.05). Vasodilation was observed in transverse arterioles (A3) (1.8 ± 0.20: P < 0.05). Correspondingly, all arteriole and venule flow was increased by 120 min (P < 0.05) of reperfusion. There was a transient decrease in the number of flowing capillaries at 0 and 30 min reperfusion (0.73 ± 0.09 and 0.84 ± 0.06: P < 0.05, respectively). Conclusions: At the onset of reperfusion heterogeneous arteriole flow and transient decrease in flowing capillaries was observed; however, return of flow in all capillaries and an eventual hyperemic response in all arterioles suggests the reversible nature of this response. Single arteriole occlusion may allow for a more controlled and detailed microcirculatory analysis during ischemia-reperfusion. © 2012 Wiley Periodicals, Inc. Microsurgery, 2013.
Published online 14 November 2012
Gesehen am 27.01.2022